KnowledgePoint : developing a seamless integration for a channel focusing on utilization of Java classes / Servlets from within OpenACS / Azrel Ahamad - Ahamad, Azrel (2005)
KnowledgePoinfi''^ is the Knowledge Portal architecture for the Systems Science Department of the Faculty of Information Technology and Quantitative Science (FTMSK). Open source initiative is making its root here at FTMSK with an ongoing development of the knowledge repository and knowledge map layer within OpenACS web application framework. OpenACS is an open-source software for web application framework that build on Tel scripting language. There is also other online system in research such as E-Portfolio to cater for lecturers' information. An open-source portal framework that utilizes Java, uPortal framework will be use as a single point entry for the KnowledgePoint'i''^. This paper is aims at finding a suitable mechanism to integrate the OpenACS web application framework with the uPortal framework. One way to do it is by using web services.